Unusual Market Activity Di Bursa Efek Indonesia Periode Tahun 2021 - 2023 - Adytia Rahman; Noer Azam Achsani; Bayu Bandono (Owner : Riset dan Jurnal Akuntansi, 2025)
The capital market plays a crucial role in a country's economy, enabling companies to raise funds through the sale of securities, with the Indonesia Stock Exchange (IDX) overseeing the trading of these securities to ensure transparency and protect investors. One of IDX's surveillance mechanisms is Unusual Market Activity (UMA), which identifies unusual stock price movements that may not necessarily violate regulations. This study highlights the function of UMA in maintaining market order, analyzing its impact on abnormal returns, and evaluating the effectiveness of UMA policies in creating a transparent, fair, and efficient market in Indonesia. The research investigates the influence of UMA announcements on stock trading activity and abnormal returns for companies listed on the IDX from January 2021 to December 2023. The data includes daily stock prices and transactions from IDX, KPEI, and KSEI, focusing on the observation period from H-5 to H+5 around UMA announcements. A purposive sampling technique was employed to select stocks on the UMA list during the study period. Using an event study methodology, the analysis includes descriptive statistics, normality tests, Wilcoxon Signed Rank Tests to measure changes in Trading Volume Activity (TVA) and abnormal returns before and after UMA announcements. The results reveal that after UMA announcements, the average abnormal return decreased from -0.112 to -0.253, and TVA declined from 0.0278 to 0.0184. The Wilcoxon test confirmed significant differences in AR and TVA before and after UMA, indicating that UMA impacts the market through declines in stock prices and trading activity.